Pancreatic islet production of murine interleukin-10 does not inhibit immune-mediated tissue destruction. - Lee, M S (1994)
IL-10 inhibits macrophage-dependent antigen presentation, cytokine production, and generation of allospecific cells in vitro. These findings have lead to the widespread expectation that IL-10 may be a useful immunosuppressive agent to inhibit allograft rejection or autoimmunity in vivo. We used two experimental paradigms to study effects of murine IL-10 on in vivo immune responses. First, fetal pancreata or adult pancreatic islets from transgenic mice expressing IL-10 in pancreatic beta cells (Ins-IL-10 mice) were grafted across the MHC barrier to examine if IL-10 could inhibit allograft rejection. Second, Ins-IL-10 mice were crossed with transgenic mice expressing lymphocytic choriomeningitis virus (LCMV) antigens in pancreatic beta cells. These mice were infected with LCMV to elicit autoimmune diabetes, allowing us to ask if IL-10 protects islets from autoimmune destruction. We observed that allografts from IL-10-transgenic donors were rejected with comparable kinetics to the rejection of control nontransgenic allografts, indicating that IL-10 does not inhibit allograft rejection. After LCMV infection, IL-10 and LCMV antigen double transgenic mice developed diabetes earlier than LCMV antigen single transgenic littermates, suggesting that IL-10 does not inhibit islet antigen presentation or recognition. Our results contrast to in vitro observations and suggest that IL-10 cannot overcome immune-mediated tissue destruction within the pancreas.